2013
DOI: 10.1179/2047773213y.0000000118
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization ofSalmonella entericain day-old ducklings in Egypt

Abstract: Importing day-old ducklings (DOD) unknowingly infected with non-typhoid Salmonella (NTS) may be associated with disease risk. Domestic and international trade may enhance this risk. Salmonella enterica serovars, their virulence genes combinations and antibiotic resistance, garner attention for their potentiality to contribute to the adverse health effects on populations throughout the world. The aim of this study was to estimate the risk of imported versus domestic DOD as potential carriers of NTS. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 58 publications
4
13
0
Order By: Relevance
“…The resistance pattern of clindamycin was similar to the observation of Cossi et al who also found all isolates in their study resistant to clindamycin [40]. The results of colistin are in disagreement with Osman et al who found most of their isolates sensitive to colistin while we recorded a higher percentage of resistance [41]. Increase in the trend of colistin resistance has been reported due to mis-sense mutations in two genes, pmrA and pmrB genes, which encode a regulator and sensor of a two-component regulatory system of outer membrane [42].…”
Section: Discussionsupporting
confidence: 77%
“…The resistance pattern of clindamycin was similar to the observation of Cossi et al who also found all isolates in their study resistant to clindamycin [40]. The results of colistin are in disagreement with Osman et al who found most of their isolates sensitive to colistin while we recorded a higher percentage of resistance [41]. Increase in the trend of colistin resistance has been reported due to mis-sense mutations in two genes, pmrA and pmrB genes, which encode a regulator and sensor of a two-component regulatory system of outer membrane [42].…”
Section: Discussionsupporting
confidence: 77%
“…Farzan et al, (2010) reported 31.5% prevalence of Salmonella in swine. Pork and beef also play a great role in causing salmonellosis apart from poultry meat (Litrup et al, 2010;Osman et al, 2014;Abatcha et al, 2018).…”
Section: Isolation Identification Confirmation and Serotyping Of Samentioning
confidence: 99%
“…was recovered from diarrheic neonatal calves [ 40 ]. Infections among imported ducklings and camels were considered as an additional source for salmonellosis in Egypt [ 41 , 42 ].…”
Section: Bacterial Zoonosismentioning
confidence: 99%